2018
DOI: 10.1039/c8ra01047a
|View full text |Cite
|
Sign up to set email alerts
|

Thermal property improvement of polytetrafluoroethylene nanocomposites with graphene nanoplatelets

Abstract: Adding GNPs into PTFE can significantly improve the thermal properties of nanocomposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…In order to conquer defects of neat PTFE, several researchers have investigated enhance properties based on PTFE, such as creep resistance, abrasion resistance, and higher thermal stability Cai et al . fabricated graphene nanoplatelet (GNP)–PTFE nanocomposites through liquid phase exfoliation of graphite sheets in ethanol with tip sonication.…”
Section: Introductionmentioning
confidence: 99%
“…In order to conquer defects of neat PTFE, several researchers have investigated enhance properties based on PTFE, such as creep resistance, abrasion resistance, and higher thermal stability Cai et al . fabricated graphene nanoplatelet (GNP)–PTFE nanocomposites through liquid phase exfoliation of graphite sheets in ethanol with tip sonication.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a kind of two-dimensional layered material with an exceptionally high Young’s modulus of ~ 1.0 Tpa, ultrahigh thermal conductivity of ~ 5000 W/(m · K), high transmittance of 97.7%, high intrinsic mobility of ~ 200,000 cm 2 /(V · s), and extremely high resistance to gas permeation [ 1 3 ]. Because of these outstanding properties, graphene has great potential for many applications including sensors, electronic devices, advanced polymer nanocomposites, energy storage, solar cells, smart coatings, ultrafast lasers, catalysis, and biological labeling [ 2 , 4 6 ]. The unique properties and potential applications have led to researchers exploring promising methods to produce graphene in the past several years.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Previous reports showed that PTFE reinforced by graphene nanoplate as a filler had the same melting temperature (Tm) to that of pure PTFE (Tm=317°C) but the degree of crystallinity (X c ) was significantly increased. 51 According to our results, improvement of thermal stability of PTFE/PVA with the addition of GO nanoparticles was not significant. It could What is the current knowledge?…”
Section: Alizarin Red S Stainingmentioning
confidence: 60%
“…be explained by increasing the -O containing groups in composite after incorporation of GO nanoparticles, and also probably the mobility behavior of carbon-carbon polymer skeleton. 51,52 The deformation behavior of the scaffolds was examined using compression tests. PP and PPG scaffolds revealed respective compressive modulus of 130 and 620 kPa which means that the PPG scaffold is stiffer than PP scaffold.…”
Section: Research Highlightsmentioning
confidence: 99%